2018
DOI: 10.1186/s13104-018-3551-y
|View full text |Cite
|
Sign up to set email alerts
|

Errors in the Hematology Laboratory at St. Paul’s Hospital Millennium Medical College, Addis Ababa, Ethiopia

Abstract: ObjectiveThe objective of this study was to determine the magnitude of pre-analytical, analytical and post-analytical laboratory errors in hematology tests.ResultsA total of 2606 hematology requests were studied. Out of the total, 562 (21.6%) pre-analytic, 14 (0.5%) analytical and 168 (6.4%) post-analytical errors were recorded which contribute a total frequency of 75.5, 1.9 and 22.6%, respectively. The name of the physician requesting the test was not provided on 2215 (85%) of request forms and 1827 (70.1%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
22
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 24 publications
(20 reference statements)
5
22
5
2
Order By: Relevance
“…This result was higher than the study done at St Paul’s Hospital Millennium Medical College, 6.4%. 16 …”
Section: Discussionmentioning
confidence: 99%
“…This result was higher than the study done at St Paul’s Hospital Millennium Medical College, 6.4%. 16 …”
Section: Discussionmentioning
confidence: 99%
“…it is obligatory to take it into consideration when interpreting the reports exploring haemostasis [4]. A study carried out in 2018 [6], showed the absence of the mention sex of the patient from the prescription card in 10.3% of the total of the prescription cards received in the laboratory. In our survey, each patient's sex was marked on the corresponding prescription form.…”
Section: Discussionmentioning
confidence: 99%
“…Mention of the age or date of birth of the patient on the prescription form is essential for correct interpretation [10][11][12]. In the series of Tadesse et al [6], 11.5% of cards did not mention the age of the patient. In our series, age was not mentioned on 27% of the total number of cards received.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations